Uji Kurang Satu Pupuk N, P, dan K terhadap Pertumbuhan Jagung di Dutohe Kabupaten Bone Bolango - ., Hermanuddin; ., Nurdin; Jamin, Fitriah S. (Jurnal Agroteknotropika, 2012)
The aim of this study was to determine (1) the effect of N, P, and K fertilizers on the maize growth and (2) the best treatment combinations on the maize growth. The fertilizers method using minus one test in randomized block design pattern with four treatments and three replications. Dosages of each treatment were 160 kg Urea, 54 kg TSP, and 90 kg KCl. The results of this research showing that the minus one test of N, P, and K fertilizers has significant effect to plant high on 14 days after planting (DAP), 42 DAP, and 56 DAP, but has not significant effect on 28 DAP. This pattern was the same with leaf color parameters. , for leaf numbers has significant effect on 28 DAP only. The best treatment combination was N+K treatment or minus P.